2022
DOI: 10.1111/nph.17985
|View full text |Cite
|
Sign up to set email alerts
|

Plant phosphorus‐use and ‐acquisition strategies in Amazonia

Abstract: In the tropical rainforest of Amazonia, phosphorus (P) is one of the main nutrients controlling forest dynamics, but its effects on the future of the forest biomass carbon (C) storage under elevated atmospheric CO 2 concentrations remain uncertain. Soils in vast areas of Amazonia are P-impoverished, and little is known about the variation or plasticity in plant P-use andacquisition strategies across space and time, hampering the accuracy of projections in vegetation models. Here, we synthesize current knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 222 publications
(390 reference statements)
1
51
0
Order By: Relevance
“…Previous studies have shown that root exudates play a decisive role in plant interactions [ 41 , 42 ]. It has been reported that flavonoids secreted by leguminous plants contribute to nitrogen fixation, and carboxylates to phosphorus acquisition [ 43 , 44 ]. Furthermore, allelopathic autotoxicity occurs due to some chemicals secreted by C. sativus itself, such as cinnamic acid [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that root exudates play a decisive role in plant interactions [ 41 , 42 ]. It has been reported that flavonoids secreted by leguminous plants contribute to nitrogen fixation, and carboxylates to phosphorus acquisition [ 43 , 44 ]. Furthermore, allelopathic autotoxicity occurs due to some chemicals secreted by C. sativus itself, such as cinnamic acid [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The best soil variable in our model is soil phosphorus, a known limiting factor for Amazonian biomass productivity favoring better agricultural potential, higher near the Andes and lower in central and eastern Amazonia ( Reichert et al, 2022 ). Phosphorus is lowest for other archaeological sites perhaps pointing to its limiting factor in agricultural potential.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanisms to obtain P incur carbon costs (Raven et al, 2018; Reichert et al, 2022; Ryan et al, 2012). These range from the minimal costs associated with root hair formation, moderate costs associated with constructing and maintaining root systems of diverse morphology or architecture, to relatively high costs associated with supporting mycorrhizal symbioses and producing root exudates (Lynch & Ho, 2005; Raven et al, 2018; Reichert et al, 2022). Root exudates and root symbioses may each consume up to 25% of photosynthate production, depending on species (Wang & Lambers, 2019).…”
Section: Introductionmentioning
confidence: 99%